Konsep Keadilan Gender dalam Perspektif Islam - Wijayanti Eka Suryandari; Mustamin Giling (Al-Kindi, 2026)
This study aims to analyze the concept of gender justice from an Islamic perspective by comparing it to Western feminist theories. The study aims to answer the question of whether Islam views gender equality as a form of social justice or whether it has its own principles distinct from the Western paradigm. This research uses a descriptive qualitative method with a library research approach. This research focuses on several issues: 1) What are the origins of gender formation? 2) Is gender influenced by biological factors or is it purely a social construct? Data were obtained from classical and contemporary literature discussing the concepts of gender, feminism, and justice in Islam, and then analyzed comparatively. The results show that Islam has upheld the principle of justice for men and women from the beginning through the teachings of monotheism, which place both men and women equal before God with complementary social roles. The differences in rights and responsibilities between the two are not a form of injustice, but rather a manifestation of the balance of functions in accordance with human nature.